Polygamy and Muslim Women in Contemporary Indonesian Literature - Wajiran Wajiran (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
This paper will examine the ways in which polygamy is addressed in contemporary Indonesian literature. The literature that will be analysed is that published after the reformation era, whereby new freedoms have encouraged many Muslim writers to raise this controversial issue. This paper will apply feminist theory especially that of the Muslim feminist Amina Wadud. Furthermore, in order to understand the contextuality of the works, a cultural materialist approach is also applied. There are some Indonesian writers who overtly depict polygamy in their literature, such as Habiburrahman El Shirazy and Alfina Dewi. Although they are all Muslims they have different perspectives in presenting the issue of polygamy in their works. These differences reflect Indonesian Islamic society where polygamy is controversial. Some Muslims accept polygamy as Islamic teaching but others do not.